2002
DOI: 10.1042/bj20020845
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 7, syntaxin 8, Vti1 and VAMP7 (vesicle-associated membrane protein 7) form an active SNARE complex for early macropinocytic compartment fusion in Dictyostelium discoideum

Abstract: The macropinocytic pathway in Dictyostelium discoideum is organized linearly. After actin-driven internalization, fluid material passes sequentially from endosomes to lysosomes, where molecules are degraded and absorbed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 49 publications
1
35
1
Order By: Relevance
“…Localization and structure of the Golgi apparatus in embryonic neuroepithelial cells and adult neurons was normal as examined by electron microscopy or by GM130 immunostaining (data not shown). In contrast, the localization of Vamp7 (also known as TI-VAMP), a vesicle SNARE involved in apical membrane transport in epithelial cells 22,23 and neurons 24,25 , was strongly apical in normal neuroepithelial cells and profoundly disrupted in hyh mutants (Fig. 5k,l), suggesting that partial loss of αSnap disrupted its apical targeting function without disrupting all its cellular functions.…”
Section: Nature Genetics Volume 36 | Number 3 | March 2004 267mentioning
confidence: 97%
“…Localization and structure of the Golgi apparatus in embryonic neuroepithelial cells and adult neurons was normal as examined by electron microscopy or by GM130 immunostaining (data not shown). In contrast, the localization of Vamp7 (also known as TI-VAMP), a vesicle SNARE involved in apical membrane transport in epithelial cells 22,23 and neurons 24,25 , was strongly apical in normal neuroepithelial cells and profoundly disrupted in hyh mutants (Fig. 5k,l), suggesting that partial loss of αSnap disrupted its apical targeting function without disrupting all its cellular functions.…”
Section: Nature Genetics Volume 36 | Number 3 | March 2004 267mentioning
confidence: 97%
“…There is some supporting evidence in yeast that Use1p/Slt1p interacts with Ykt6p (8), which participates in the membrane fusion of vacuoles. Similarly, we observed an interaction between D12 and VAMP7, which is involved in phagocytosis or trafficking between endosomes and lysosomes (55)(56)(57). Interestingly, we observed that the 17.2-kDa fragment of D12 failed to bind to VAMP7, although it did bind syntaxin 18 and Sec22b, and fragments longer than 17.8 kDa bound to VAMP7 (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…It is possible that the fusion events also involved one of the hits in our RNAi screen, vesicle‐associated membrane protein 7 (VAMP7). It has been shown to mediate pinosome fusion events in Dictyostelium discoideum 58.…”
Section: Discussionmentioning
confidence: 99%